Access to Written Submissions in Preliminary Reference Proceedings: An Evaluation of the CJEU Statute Reform and its Contribution to Open Justice - Ilaria Fevola; Stefano Montaldo (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(2), 357-389 | Article | (Table of Contents) 1. Introduction. – 2. Open justice and human rights: ensuring transparency and accountability through public access. – 2.1. The notion of open justice: scope and constitutive elements. – 2.2. Open justice under international and EU law. – 3. Open justice at the CJEU: evolution, targets achieved and unresolved questions. – 4. The CJEU and access to Court proceedings: the state of play. – 4.1. The lack of EU law provisions allowing for access to Court proceedings. – 4.2. Indirect access to Court proceedings through the Transparency Regulation 1049/2001. – 4.3. Voluntary disclosure by the parties to a case. – 5. The reform of the CJEU Statute and the paradigm shift concerning access to written submissions in the context of preliminary reference proceedings. – 5.1. The interinstitutional negotiations. – 5.2. The final text of Article 23(5) of the CJEU Statute. – 6. The reform between theory and practice: the limits to proactive publication of Court proceedings. – 6.1. The expanded definition of ‘interested person’ under Article 23 of the CJEU Statute – 6.2. The limits to proactive disclosure of Court proceedings: the objection to publication. – 7. Concluding remarks. | (Abstract) The article analyses the new provisions of the Statute of the Court of Justice and its Rules of Procedure requiring the proactive publication, on the Court’s website, of written observations submitted in preliminary reference proceedings by the parties and other interested persons. This development represents a significant step forward for the Court of Justice, which has historically prioritised confidentiality to protect the serenity of proceedings and the equality of arms between parties. Against this backdrop, the Article delves into this aspect of the reform through the theoretical foundations of open justice alongside the evolution of the rules and case- law on access to court documents. It also explores the implications of the reform, with particular attention to the possibility for the parties and interested persons to object to publication. To that end, the Article includes an empirical analysis of the number of objections and published observations during the first six months of the new regime’s implementation. A combined reading of the normative and empirical findings suggests that the widespread concerns over an extensive use of objections appear (for now) to be unfounded, and that a real paradigm shift towards greater openness at the Court of Justice may indeed be underway.